Some simple epidemic models - Fred Brauer (Mathematical Biosciences and Engineering)
The SARS epidemic of 2002-3 led to the study of epidemic models including management measures and other generalizations of the original 1927 epidemic model of Kermack and McKendrick. We consider some natural extensions of the Kermack-McKendrick model and show that they share the main properties of the original model.